An efficient, green synthesis of novel regioselective and stereoselective indan-1, 3-dione grafted spirooxindolopyrrolizidine linked 1, 2, 3-triazoles via a one-pot five-component condensation using PEG-4001. Issue 50 (4th June 2015) - Rajeswari, M.; Sindhu, Jayant; Singh, Harjinder; Khurana, Jitender M.
<x xml:space="preserve">Abstract</x> An efficient synthesis of highly diversified novel functionalized indan-1, 3-dione grafted spirooxindolopyrrolizidine linked 1, 2, 3-triazole conjugates is reported using Cu(i) as a catalyst in PEG-400.